Nilai Tambah dan Kelayakan Pengolahan Ubi Jalar Menjadi Cakar Ayam - Simbolon, Friska (MuJAgri: Musamus Journal of Agribusiness, 2019)
Sweet potato is one food commodity that has a complete nutritional content compared to other food commodities. Sweet potatoes can be processed into various forms or kinds of processed products, including chicken paws. Perbaungan District, Serdang Bedagai Regency is the center of production of all agricultural products including chicken paws. The purpose of this research is to know the process of processing sweet potatoes into chicken paws, knowing the added value of chicken paw processing and knowing the feasibility of chicken paw processing. The determination of the research area was carried out purposively. The method of determining the sample is the census method with a total sample of 12 processors. The analytical method used for calculating income is the difference between total revenue and total production costs, calculation of value added that is the value of the product minus the value of raw materials, the value of supporting materials and the value of equipment depreciation. Calculation of business feasibility is a comparison between revenue and total production costs. From the results of the study it can be concluded: 1) The process of processing sweet potatoes into chicken claws is classified as traditional because all stages of processing are still using human hands. 2) The added value of the chicken paw processing business is relatively low, that is, the added value of Rp 19,670,775.35 and the value added ratio of 40.75% â‰¤ 50%. 4) Chicken paw processing in the study area is feasible because it obtained an R / C value of 1.42> 1. Keywords: Sweet Potatoes; Chicken feet; Value-added; Appropriateness